Website "Technical drawing" for development of spatial and constructive thinking - Mackus, Austris; Snipkis, Andris; Znotiņa, Inta; Jurāne, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays, not every school of Latvia offers it’s pupils to acquire the basics of technical drawing. As a result, university lecturers often find that students lack the spatial and constructive thinking skills needed to successfully participate in graphics and design related courses. To try to improve the situation in early 2013, Riga Technical University lecturer Ieva Jurāne (Mg.sc.ing.), in collaboration with University of Liepaja Natural and Engineering Faculty, decided to develop a website "Technical Drawing" (http: //rasesana.it- studenti.liepu.edu.lv), in which every interested person, irrespective of whether it is a student or a pupil, could independently solve a variety of technical drawing course related tasks, thus developing their spatial and constructive thinking skills, which later makes it easier to learn complex Engineering Graphics programs such as AutoCAD or SolidWorks. This publication is made to present the web sites "Technical Drawing" purpose, content and development process.